Knowledge and attitude of nursing staff towards nebulization therapy in a tertiary care hospital - Aithal, Suhas; S. V., Jagmohan; S., Niveditha (International Journal of Research in Medical Sciences, 2017)
Background: Nebulization is an important tool in the treatment of respiratory conditions. Nurses are primary health care providers for using the nebulizers in a hospital setting. The examination of nurse’s knowledge and performance regarding the nebulizer therapy is of utmost importance for proper nebulization. Aim of the study was to access the knowledge and attitude of staff nurses towards nebulization therapy. Methods: A cross sectional study was conducted at the RL Jalappa hospital, Kolar, Karnataka, India. 50 nurses working the intensive care units and wards were given a questionnaire regarding the key aspects of nebulization therapy. A workshop was then conducted for the same participants on correct nebulization techniques and the questionnaire was given and the results post workshop was analyzed. Results: In pre-study, most nurses had unsatisfactory knowledge with respect to breathing pattern during nebulization (72.2%), types of masks used (83.3%), changing of filter (62.5%). On comparing satisfactory knowledge level of nurses pre-and post, it was found statistically significant increase in knowledge for breathing pattern during nebulization, knowledge of types of nebulization, nebulization time, nebulization end point, types of drugs used, type of dilution, proportion of dilution, ideal volume of drugs in medication, replacement of tubing, changing of filter, types of disinfections used, types of nebulization and types of mask (p <0.05). Conclusions: The knowledge of the staff nurses regarding the nebulization therapy was unsatisfactory which was reflected by improvement in the knowledge post workshop training. The staff nurses should be provided periodic training on nebulization therapy to give effective and safe care to patients.